Models for da Costa’s paraconsistent set theory - Figallo-Orellano, Aldo; Slagter, Juan Sebastián (Anais do Workshop Brasileiro de Lógica (WBL), 2020)
In this work we will be constructed F-structures-valued models as generalization of Boolean-valued models and proved that these models that verify Leibniz’ Law validate all the set-theoretic axioms of da Costa’s Paraconsistent Set Theory type ZF.